'. . . if you bring the kit home, you [can] get time and test together with your partner': Pregnant women and male partners' perceptions regarding female partner-delivered HIV self-testing in Uganda – A qualitative study. (November 2017) - Matovu, Joseph KB; Buregyeya, Esther; Arinaitwe, Jim; Wanyenze, Rhoda K
In 2015, the World Health Organization reported that more than 60 million people were tested for HIV in 122 low- and middle-income countries between 2010 and 2014. Despite this level of progress, over 40% of people living with HIV remain unaware of their HIV status. This calls for innovative approaches to improve uptake of HIV testing services, including use of HIV self-test (HIVST) kits. We conducted a cross-sectional, qualitative study to assess pregnant women and their male partners' perceptions regarding female partner-delivered HIVST kits. This study was conducted at two health facilities in Central Uganda between November and December 2015. Data were collected on pregnant women's willingness to take HIVST kits to their male partners and other household members using eight focus group discussions and 30 in-depth interviews. Data were analyzed following a thematic framework approach. Overall, pregnant women were willing to take HIVST kits to their partners and other household members, with the exception of their cowives. Male partners were willing to use HIVST kits brought by their female partners. Our findings suggest that secondary distribution of HIVST kits through female partners is acceptable and has the potential to improve male partner and household-member HIV testing.